STRATEGI MANAJEMEN PEMASARAN DI PONDOK PESANTREN MODERN AL-KINANAH JAMBI : FAKTOR PENDUKUNG DAN PENGHAMBAT DALAM MENARIK MINAT PENDAFTARAN - Ananda Syafira, Friska; MY, Mahmud; Fitriani, Suci (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the principal's marketing management strategy at the Al-Kinanah Modern Islamic Boarding School Jambi, specifically identifying sthe supporting and inhibiting factors in attracting prospective students. The research is motivated by a decline in the number of registrants over the last three years (2023-2025). This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews, observation, and documentation. The results show that the supporting factors in marketing management consist of superior programs (foreign language development and integrated curriculum), hight-quality human resources with educational backgrounds ranging from undergraduate to doctoral degrees (domestic and international graduates), and strong community support through word-of-mouth promotion. Meanwhile, the inhibiting factors identified are the high cost of digital advertising (Facebook Ads) and the limited time of human resources, as the marketing team also serves as teaching staff. This study concludes that although there are financial and time constrains, the optimization of internal potential and community trust remains the main pillar in maintaining the institution's existence. Suggestions for the institution include a more structured budget allocation for digital promotion and the formation of a dedicated marketing team to avoid overlapping duties